Study of UV Transmission through a Few Edible Oils and Chicken Oil - K. Anil Kumar; K. Viswanathan (Journal of Spectroscopy)
Effects of solar UV radiation on the biosphere are well known and a lot of studies are going on to reduce its dangerous effects on human beings. Atmospheric ozone layer is not uniform over the globe, so that less ozone over tropics makes it receive more UV insolation, than high latitude places. People in the tropics are continuously exposed to high UV dosage, leading to skin reddening and the dangerous “sun stroke.” In southern India people use some vegetable oils to protect the skin from sun heat. Studies of “sun stroke” show that people having skin of moderate colour are the main victims. In some parts of Southern Kerala like Kottayam, Ernakulam, and Alappuzha traditional people were using oil extracted from chicken, called “chicken oil,” for the treatment of “heat burns” and other types of burns. This motivated us to study the UV absorption characteristics of chicken oil, and compare them with that of other commonly used vegetable oils. It is found that the chicken oil shows maximum absorption of UV radiation of about 85%, and neem oil shows absorption of about 60%. Other oils show comparatively very low absorption of UV radiation. So this property of chicken oil may be the reason for using it as remedy for heat burns.